Characterization of the trade in manta and devil ray gill plates in China and South‐east Asia through trader surveys - O'Malley, Mary p.; Townsend, Kathy A.; Hilton, Paul; Heinrichs, Shawn; Stewart, Joshua D. (Aquatic conservation, 2017)
Dried gill plates from manta and devil rays, some of the world's most biologically vulnerable fishes, have become a valued commodity in Asian dried‐seafood and traditional Chinese medicine markets. This trade is a primary driver of fisheries, which have led to declines in many mobulid populations. With no reliable trade statistics and scarce data on mobulid fisheries, this study estimates the number and species of mobulids required to supply this trade, and investigates the consumers and suppliers involved and drivers of demand. Following preliminary market research, 525 trader surveys were conducted in Hong Kong, Singapore, Macau, Taiwan, and southern China. Guangzhou, China was identified as the centre of the trade accounting for 99% of total estimated market volume of 60.5 tons of dried gill plates in 2011, increasing to 120.5 tons by 2013. The estimated number of mobulids converted from tons of gill plates more than doubled over the period to 130 000, comprising 96% devil rays, Mobula japanica, Mobula thurstoni, and Mobula tarapacana, and 4% Manta spp. By 2015 the Guangzhou market had declined sharply, reportedly due to conservation campaigns and government policies. However Hong Kong's gill plate sales increased dramatically between 2011 and 2015. China, Indonesia, Vietnam, Sri Lanka, and India were reported most frequently as gill plate sources. Vendors recommend gill plates (trade name pengyusai) for ailments ranging from acne to cancer and as a general health tonic. While pengyusai is a new addition to traditional Chinese medicine literature and is rarely prescribed by traditional medicine practitioners, it is readily available over the counter and aggressively marketed by vendors. Working in concert with consumer demand reduction efforts, increased measures to restrict mobulid fisheries and trade are recommended to prevent further population declines of these highly vulnerable species. Copyright © 2016 John Wiley & Sons, Ltd.